Composições e atravessamentos com uma formação continuada sobre a medicalização da educação e da vida - Coutinho, Márcia Izabel (2021)
This research aims to analyze the aspects which enveloped a university extension course entitled “Medicalization of Education and Life” through the perspective of professionals and students of the fields of Education, Psychology and Health. This is a qualitative study. It is worthy to mention that to carry out the field research, it was required the documental analysis of the records presented by the university extension course alumni. As for the data study, it organizes specific categories and also uses the dynamic of the Content Analysis method. Departing from the critical theoretical references, it brings about a conceptual review and also sparks the debates related to the medicalization phenomenon within the context of Education and society. It understands the complexity of such phenomenon and highlights, amongst its components, the transformation of questions of diferente orders, issues into pathologies of the individuals. It argues against the medicalization process to maintain the autonomy and the diversity of the individuals. The inventive contribution of this research ─ the educational product ─ proposes an e-book entitled “An Initial Conversation about the Medicalization Phenomenon, its Compositions and Effects” which aims at fostering the continuing education measures for feeding the critical thinking about the phenomenon of the medicalization of Education and society and as well as promoting the development of the demedicalization process. The considerations and inferences which arose from the analysis of the documentation suggest, among others, the following: the necessity of promoting debates, especially for Education, Psychology and Health professionals, to discuss the historical, social, political and economic aspects of the medicalization phenomenon, targeting at the deconstruction of the practices which perpetuate the process of societal exclusion and the will and commitment of the individuals that attended the university extension course with the composition for better life possibilities for all the people.